ANALISIS MEREK PADA PRODUK DETERGEN BUBUK SURF - Purwani, Khusniyah (Universitas Muhammadiyah Surakarta, 2004)
This research was aimed at examining and evaluating a new brand name of powder detergentproduct, Surf. The evaluation was based on five categories of good brand name consisting ofmemorability, uniqueness, pronounceability, image, and consistency with overall corporate brandingstrategy. The questionnaire used the above five categories combined with Chiranjeev Kohliâs criteria.